The Impact of Digital Transformation on Supply Chain Management in Small and Medium Enterprises: A Systematic Literature Review - Khairen Niza Mefid Mefid; Fitria Ridhaningsih (SEKOLAH TINGGI TEKNOLOGI INDUSTRI PADANG, 2024)
This study examines the impact of digital transformation on supply chain management (SCM) within Small and Medium Enterprises (SMEs) by utilizing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology. Digital transformation involves integrating advanced digital technologies to improve business operations and processes. For SMEs, which often face resource limitations and scalability issues, digital transformation can significantly enhance SCM processes by increasing efficiency, reducing costs, and improving agility and collaboration. The research employs a systematic review and meta-analysis of existing literature to assess the effects of digital transformation on SCM in SMEs. The PRISMA methodology ensures a thorough and unbiased selection of relevant studies, providing a solid foundation for the analysis. The key SCM dimensions explored include operational efficiency, cost management, agility, and collaboration. The results reveal that digital transformation leads to substantial improvements in SCM performance. Automation of processes, enhanced real-time data exchange, and better decision-making capabilities are some of the benefits identified. However, the study also highlights challenges such as the high initial costs associated with digital technologies, resistance to change within organizations, and the need for continuous skill development. The findings suggest that successful digital transformation in SMEs' SCM requires strategic planning, investment in employee training, and a supportive organizational culture. This research contributes to the understanding of how digital transformation can be leveraged to optimize SCM in SMEs and provides actionable insights for practitioners and policymakers aiming to foster digital innovation in this critical sector